Vitamin C in the Management of Thyroid Cancer: A Highway to New Treatment? - Francesca Gorini; Alessandro Tonacci (MDPI AG, 2024)
Thyroid cancer (TC) is the most common endocrine malignancy, with an increased global incidence in recent decades, despite a substantially unchanged survival. While TC has an excellent overall prognosis, some types of TC are associated with worse patient outcomes, depending on the genetic setting. Furthermore, oxidative stress is related to more aggressive features of TC. Vitamin C, an essential nutrient provided with food or as a dietary supplement, is a well-known antioxidant and a scavenger of reactive oxygen species; however, at high doses, it can induce pro-oxidant effects, acting through multiple biological mechanisms that play a crucial role in killing cancer cells. Although experimental data and, less consistently, clinical studies, suggest the possibility of antineoplastic effects of vitamin C at pharmacological doses, the antitumor efficacy of this nutrient in TC remains at least partly unexplored. Therefore, this review discusses the current state of knowledge on the role of vitamin C, alone or in combination with other conventional therapies, in the management of TC, the mechanisms underlying this association, and the perspectives that may emerge in TC treatment strategies, and, also, in light of the development of novel functional foods useful to this extent, by implementing novel sensory analysis strategies.